Reconstruction towards sustainable communities : promotion of locally-based industries with all stakeholder approach (UNCRD NagoyaJP, 2012)
Shares the experiences of community reconstruction from the Great East Japan earthquate and tsunami and exchanges information between representatives of local communities and experts. Also exchanges practical ideas to support economic activities of local communities, particularly community-based eco-friendly industries and, information regarding the role of NGOs and NPOs in reconstruction efforts.
Keywords: INDUSTRIAL PROMOTION